Metabolic Dysfunction in Motor Neuron Disease: Shedding Light through the Lens of Autophagy - Subhavi De Silva; Bradley J. Turner; Nirma D. Perera (Metabolites, 2022)
Amyotrophic lateral sclerosis (ALS) patients show a myriad of energetic abnormalities, such as weight loss, hypermetabolism, and dyslipidaemia. Evidence suggests that these indices correlate with and ultimately affect the duration of survival. This review aims to discuss ALS metabolic abnormalities in the context of autophagy, the primordial system acting at the cellular level for energy production during nutrient deficiency. As the primary pathway of protein degradation in eukaryotic cells, the fundamental role of cellular autophagy is the adaptation to metabolic demands. Therefore, autophagy is tightly coupled to cellular metabolism. We review evidence that the delicate balance between autophagy and metabolism is aberrant in ALS, giving rise to intracellular and systemic pathophysiology observations. Understanding the metabolism autophagy crosstalk can lead to the identification of novel therapeutic targets for ALS.